Ship Hull Geometry Design by Using B-Spline Curve Fitting and Lofted Surface Generation - Sheely Leony Artha Pasaribu; Berlian Arswendo Adietya; Muhammad Iqbal; Hasanudin Hasanudin; Wiwin Sulistyawati; Mohammad Sholikhan Arif; Ardi Nugroho Yulianto (Kapal: Jurnal Ilmu Pengetahuan dan Teknologi Kelautan, 2026)
As one of the largest archipelago countries in the world, Indonesia requires technological capability to independently develop efficient ship design systems. Currently, the Computer-Aided Design (CAD) software used for domestic ship design is still largely dominated by foreign commercial products, which require costly subscription fees. This dependence limits the technological independence of the national shipbuilding industry. This study aims to develop a simple CAD-based program for representing ship hull geometry using a parametric mathematical approach. The program reconstructs sectional curves using mathematics formulations and generates a continuous three-dimensional hull surface through a lofting method based on equal arc-length discretization and triangular mesh representation. The research methodology includes system design, curve and surface generation, geometric visualization, and validation through comparison with results obtained from commercial CAD software. The results demonstrate that the developed system is capable of accurately reconstructing sectional curves and generating a consistent lofted hull surface suitable for representing simple ship hull forms. This work provides an initial step toward the development of domestic ship hull design tools to support preliminary geometric modeling in Indonesia’s maritime industry.